2012
DOI: 10.15376/biores.7.4.5478-5487
|View full text |Cite
|
Sign up to set email alerts
|

Stone-Ground Wood Pulp-Reinforced Polypropylene Composites: Water Uptake and Thermal Properties

Abstract: Two of the drawbacks of using natural-based composites in industrial applications are thermal instability and water uptake capacity. In this work, mechanical wood pulp was used to reinforce polypropylene at a level of 20 to 50 wt. %. Composites were mixed by means of a Brabender internal mixer for both non-coupled and coupled formulations. Differential scanning calorimetry (DSC) and thermogravimetric analysis (TGA) were used to determine the thermal properties of the composites. The water uptake behavior was e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
28
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 22 publications
(30 citation statements)
references
References 13 publications
2
28
0
Order By: Relevance
“…Other studies have shown this trend. 18,19,26,27,[29][30][31] Tensile strength is a measure of the stress load a material can support before generating voids that lead to crazing of the material and ultimate failure. The u increase is attributed to better transfer of stress between the hydrophobic wood fiber and the hydrophilic PP matrix due to the chemical coupling.…”
Section: Tisserat Et Al 1283mentioning
confidence: 99%
“…Other studies have shown this trend. 18,19,26,27,[29][30][31] Tensile strength is a measure of the stress load a material can support before generating voids that lead to crazing of the material and ultimate failure. The u increase is attributed to better transfer of stress between the hydrophobic wood fiber and the hydrophilic PP matrix due to the chemical coupling.…”
Section: Tisserat Et Al 1283mentioning
confidence: 99%
“…One of the limitations related with the use of natural fibers is the low range of temperature allowed to process the composite to avoid fiber degradation (López et al 2012a). To avoid this problem, it is important to determine the melting and degradation temperatures of the composite material.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, wood fiber and natural fibers have gained a significant interest as a reinforcing material for commercial thermoplastics [1][2][3][4][5][6]. Some advantages of natural fibers as opposed to other reinforcing materials are their high availability, their biodegradability, and their relative low cost and density.…”
Section: Introductionmentioning
confidence: 99%